ISU HUKUM DALAM PENGATURAN FINANCIAL TECHNOLOGY (PEER-TO-PEER LENDING) DI INDONESIA - Agata Wanda Yunitha Purba; Dona Budi Kharisma (Jurnal Privat Law, 2026)
This article examines the legal issues regarding the regulation of peer-to-peer lending in Indonesia. This research is a prescriptibe normative legal research with statutory approach. The data used were primary, secondary, and tertiary legal materials. Data collection techniques carried out by literature study or document study with deductive syllogism legal material analysis techniques. The results of the research and discussion show that the regulation of P2P Lending in Indonesia is not comprehensive enough to regulate the P2P Lending industry, which leads to the emergence of several legal issues as follows: a) There is no mechanism for registering a lending platform before it can be accessed by the public; b) breach of security and privacy of personal data; c) the rise of illegal P2P Lending platforms; d) there are no clear dispute resolution steps; e) there is no proper billing mechanism.